Genome-Wide Survey of Flavonoid Biosynthesis Genes and Gene Expression Analysis between Black- and Yellow-Seeded Brassica napus - Qu, Cunmin; Zhao, Huiyan; Fu, Fuyou; Wang, Zhen; Zhang, Kai; Zhou, Yan; Wang, Xin; Wang, Rui; Xu, Xinfu; Tang, Zhanglin; Lu, Kun; Li, Jia-Na (Frontiers in Plant Science, 2016)
Flavonoids, the compounds that impart color to fruits, flowers, and seeds, are the most widespread secondary metabolites in plants. However, a systematic analysis of these loci has not been performed in Brassicaceae. In this study, we isolated 649 nucleotide sequences related to flavonoid biosynthesis, i.e., the Transparent Testa (TT) genes, and their associated amino acid sequences in 17 Brassicaceae species, grouped into Arabidopsis or Brassicaceae subgroups. Moreover, 36 copies of 21 genes of the flavonoid biosynthesis pathway were identified in A. thaliana, 53 were identified in B. rapa, 50 in B. oleracea, and 95 in B. napus, followed the genomic distribution, collinearity analysis and genes triplication of them among Brassicaceae species. The results showed that the extensive gene loss, whole genome triplication, and diploidization that occurred after divergence from the common ancestor. Using qRT-PCR methods, we analyzed the expression of eighteen flavonoid biosynthesis genes in 6 yellow- and black-seeded B. napus inbred lines with different genetic background, found that 12 of which were preferentially expressed during seed development, whereas the remaining genes were expressed in all B. napus tissues examined. Moreover, fourteen of these genes showed significant differences in expression level during seed development, and all but four of these (i.e., BnTT5, BnTT7, BnTT10, and BnTTG1) had similar expression patterns among the yellow- and black-seeded B. napus. Results showed that the structural genes (BnTT3, BnTT18 and BnBAN), regulatory genes (BnTTG2 and BnTT16) and three encoding transfer proteins (BnTT12, BnTT19, and BnAHA10) might play an crucial roles in the formation of different seed coat colors in B. napus. These data will be helpful for illustrating the molecular mechanisms of flavonoid biosynthesis in Brassicaceae species.